Addressing Student Learning Gaps in Fractions: How Effective is Synchronous Videoconferencing? - Japar, Irfan; Asamoah, Daniel; Shahrill, Masitah (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
The addition and subtraction of fractions are considered one of the most difficult topics in mathematics for students. However, interventions to improve student performance in this direction are not widespread. This action research study investigated the effectiveness of synchronous videoconference intervention in improving student performance in addition and subtraction of fractions. It also explored the perceptions of students about synchronous e-learning sessions. A total of 51 Year 7 students conveniently sampled from a government school in Brunei Darussalam served as participants for this study. The action taken included a pre-test, a videoconference lesson intervention, a post-test, survey, and interviews. The paired sample t-test revealed a significant difference in test scores t(50) = -3.50, p<0.001, with post-test scores (Mean = 8.47, SD = 1.78) higher than the pre-test scores (Mean = 7.1, SD = 3.10). These findings suggest that student performance improved after the videoconferencing intervention. The results of the survey and interviews revealed that the students had a positive perception of the videoconference lessons. They described the lessons as pleasant, collaborative, and convenient. However, they reported challenges, such as unstable internet connection, distractions, and inadequate teacher supervision. Despite these challenges, they equally preferred videoconferencing and traditional face-to-face lessons. This study concluded that videoconferencing could be a useful tool in teaching and learning fractions. It has the potential in improving student-centered teaching and learning, especially when the challenges that come with its use are controlled.DOI : https://doi.org/10.22342/jpm.16.1.17027.103-120